2016
DOI: 10.1161/strokeaha.115.012482
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Acute Stroke Severity Scale to Predict Large Artery Occlusion

Abstract: Background and Purpose— We designed and validated a simple prehospital stroke scale to identify emergent large vessel occlusion (ELVO) in patients with acute ischemic stroke and compared the scale to other published scales for prediction of ELVO. Methods— A national historical test cohort of 3127 patients with information on intracranial vessel status (angiography) before reperfusion therapy was identified. National Institutes of Health Stroke Scale (NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
125
1
18

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 172 publications
(145 citation statements)
references
References 22 publications
1
125
1
18
Order By: Relevance
“…The RACE scale score was not detailed item-by-item in 16 cases and therefore we studied 341 patients (53.4% men; age (mean±SD) 70±13 years; NIHSS score at admission (median [interquartile range] 8 [3][4][5][6][7][8][9][10][11][12][13][14][15][16] had 85% sensitivity, 68% specificity and correctly classified 71% patients. The RACE and NIHSS scores were strongly correlated (r=0.78; p<0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RACE scale score was not detailed item-by-item in 16 cases and therefore we studied 341 patients (53.4% men; age (mean±SD) 70±13 years; NIHSS score at admission (median [interquartile range] 8 [3][4][5][6][7][8][9][10][11][12][13][14][15][16] had 85% sensitivity, 68% specificity and correctly classified 71% patients. The RACE and NIHSS scores were strongly correlated (r=0.78; p<0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Other scales may identify these patients, but have not been validated prospectively or in the field (8)(9)(10)(11)(12). The RACE scale is simple and specifically designed to identify anterior circulation LVO patients (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…The presented test has a higher sensitivity and NPV than other tests (Table 4) (Hastrup et al., 2016; Katz et al., 2015; Lima et al., 2016; McMullan et al., 2017; Nazliel et al., 2008; Pérez de la Ossa et al., 2014; Scheitz et al., 2017; Singer et al., 2005). We found that the FAST PLUS test had a high sensitivity of 93% and high NPV of 94%.…”
Section: Discussionmentioning
confidence: 99%
“…This is comparable to the RACE study (McMullan et al., 2017) Other studies were performed retrospectively or with small numbers of patients (Hastrup et al., 2016; Katz et al., 2015; Lima et al., 2016; McMullan et al., 2017; Nazliel et al., 2008; Pérez de la Ossa et al., 2014; Singer et al., 2005). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation